Where has my time gone? - Zilberman, N; Grosvenor, M; Popescu, DA; Manihatty-Bojan, N; Antichi, G; Wójcik, M; Moore, AW (Springer, 2017)
Time matters. In a networked world, we would like mobile devices to provide a crisp user experience and applications to instantaneously return results. Unfortunately, application performance does not depend solely on processing time, but also on a number of different components that are commonly counted in the overall system latency. Latency is more than just a nuisance to the user, poorly accounted-for, it degrades application performance. In fields such as high frequency trading, as well as in many data centers, latency translates easily to financial losses. Research to date has focused on specific contributions to latency: from improving latency within the network to latency control on the application level. This paper takes an holistic approach to latency, and aims to provide a break-down of end-to-end latency from the application level to the wire. Using a set of crafted experiments, we explore the many contributors to latency. We assert that more attention should be paid to the latency within the host, and show that there is no silver bullet to solve the end-to-end latency challenge in data centers. We believe that a better understanding of the key elements influencing data center latency can trigger a more focused research, improving the user’s quality of experience.